Ternary All-Polymer Solar Cells With 8.5% Power Conversion Efficiency and Excellent Thermal Stability - Liu, Xi; Zhang, Chaohong; Pang, Shuting; Li, Ning; Brabec, Christoph J.; Duan, Chunhui; Huang, Fei; Cao, Yong (Frontiers in Chemistry, 2020)
All-polymer solar cells (all-PSCs) composed of polymer donors and acceptors have attracted widespread attention in recent years. However, the broad and efficient photon utilization of polymer:polymer blend films remains challenging. In our previous work, we developed NOE10, a linear oligoethylene oxide (OE) side-chain modified naphthalene diimide (NDI)-based polymer acceptor which exhibited a power conversion efficiency (PCE) of 8.1% when blended with a wide-bandgap polymer donor PBDT-TAZ. Herein, we report a ternary all-PSC strategy of incorporating a state-of-the-art narrow bandgap polymer (PTB7-Th) into the PBDT-TAZ:NOE10 binary system, which enables 8.5% PCEs within a broad ternary polymer ratio. We further demonstrate that, compared to the binary system, the improved photovoltaic performance of ternary all-PSCs benefits from the combined effect of enhanced photon absorption, more efficient charge generation, and balanced charge transport. Meanwhile, similar to the binary system, the ternary all-PSC also shows excellent thermal stability, maintaining 98% initial PCE after aging for 300 hours at 65 °C. This work demonstrates that the introduction of a narrow-bandgap polymer as a third photoactive component into ternary all-PSCs is an effective strategy to realize highly efficient and stable all-PSCs.